Analisis Fungsi Manajerial Dalam Pengembangkan Pariwisata Berkelanjutan Desa Mekar Buana-Karawang - Nandang, Nandang; Jamaludin, Asep; Wanta, Wanta (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
The aim of this research is 1) To find out, analyze and explain the implementation of managerial functions in Mekarbuana Village tourism management? 2) To find out, analyze and explain the understanding of the management and community of the Mekarbuana Village tourist destination regarding sustainable tourism? 3) To find out, analyze and explain the implementation of managerial functions to develop sustainable tourism in Mekarbuana Village? The research method used is descriptive research with a qualitative approach. Qualitative research is carried out by investigating social phenomena and human problems, producing descriptive data in the form of written and spoken words from the behavior and people observed. This study found that in developing sustainable tourism in Mekar Buana-Karawang Village, the managerial role is very important to ensure sustainability, efficient management and a positive impact on the environment of the local community. The four managerial functions referred to are Planning, Organizing, Placement and Controlling (Planning, organizing, actuating and controlling) which have been running well according to their functions. The management together with the village government is responsible for formulating the vision and mission of sustainable tourism in Mekar Buana-Karawang Village. Set long-term and short-term goals that are in line with sustainability principles. Designing tourism programs that focus on environmental preservation, local culture and community welfare. It is recommended that further research consider other aspects besides managerial functions, for example in terms of operational, financial and marketing functions. Because the managerial function has been running well in Mekar Buana Village tourism. By maintaining and improving managerial functions that are already running well, Mekar Buana Village can continue to achieve positive benefits and make a significant contribution to sustainable tourism development and the welfare of the local community. This research answers suggestions from previous research to identify and test the analysis of managerial functions in developing sustainable tourism in the village of Mekar Buana-Karawang.